A review on hepatocyte nuclear factor-1beta and tumor. Issue 1 (December 2015) - Yu, Dan-Dan; Guo, Shi-Wei; Jing, Ying-Ying; Dong, Yu-Long; Wei, Li-Xin
Abstract Hepatocyte nuclear factor-1beta (HNF1β) was initially identified as a liver-specific transcription factor. It is a homeobox transcription factor that functions as a homodimer or heterodimer with HNF1α. HNF1β plays an important role in organogenesis during embryonic stage, especially of the liver, kidney, and pancreas. Mutations in the HNF1β gene cause maturity-onset diabetes of the young type 5 (MODY5), renal cysts, genital malformations, and pancreas atrophy. Recently, it has been shown that the expression of HNF1β is associated with cancer risk in several tumors, including hepatocellular carcinoma, pancreatic carcinoma, renal cancer, ovarian cancer, endometrial cancer, and prostate cancer. HNF1β also regulates the expression of genes associated with stem/progenitor cells, which indicates that HNF1β may play an important role in stem cell regulation. In this review, we discuss some of the current developments about HNF1β and tumor, the relationship between HNF1β and stem/progenitor cells, and the potential pathogenesis of HNF1β in various tumors.